The mobility and plant uptake of gallium and indium, two emerging contaminants associated with electronic waste and other sources. (October 2018) - Jensen, Hayley; Gaw, Sally; Lehto, Niklas J.; Hassall, Leanne; Robinson, Brett H.
Abstract: Gallium (Ga) and indium (In) are increasingly susceptible to soil contamination via disposal of electronic equipment. Chemically similar to aluminium (Al), these elements may be mobile and bioavailable under acidic conditions. We sought to determine extent and nature of Ga and In mobility in the soil – plant system and thus their potential to enter the food chain. Batch sorption experiments on a high fertility silt loam (pH 5.95, CEC 22 meq 100 g −1 ) showed strong retention of both elements to the soil matrix, with mean distribution coefficient (KD ) values of 408 and 2021 L kg −1 for Ga and In respectively. KD increased with concentration, which we attributed to precipitation of excess ions as insoluble hydroxides. KD decreased with increased pH as Ga/In(OH) 2+ and Ga/In(OH)2 + transitioned to Ga/In(OH)4 - . Movement into the aboveground portions of perennial ryegrass ( Lolium perenne L.) was low, with bioaccumulation factors of 0.0037 for Ga and 0.0002 for In; foliar concentrations peaked at 11.6 mg kg −1 and 0.015 mg kg −1 respectively. The mobility of Ga and In in the soil - plant system is low compared to other common trace element contaminants such as cadmium, copper, and zinc. Therefore, Ga and In are likely to accumulate in soils and soil ingestion, either directly, via inhaled dust, or dust attached to food, will be the largest pathway into the food chain. Future work should focus on the effect of redox conditions on Ga and In, as well as uptake into acidophilic plants such as Camellia spp., which accumulate Al. Highlights: Gallium and indium are more strongly bound to soil than other common trace element contaminants. Gallium and indium are poorly translocated into the aerial portions of Lolium perenne . Gallium and indium are likely to accumulate in soil. Soil ingestion is the most likely exposure pathway for humans and animals.